THE EFFECT OF COMIC MEDIA ON MATHEMATICS LEARNING OUTCOMES FOR CLASS VI STUDENTS ON THE CONCEPT OF FACTORS AND NUMBER MULTIPLES AT SDN TELUK SANTONG - Ahyar Ardiansyah (PROGRES PENDIDIKAN, 2022)
This study aims to determine whether the use of comics in Mathematics learning for grade VI elementary school on factors and multiples of numbers helps students learn and understand difficult concepts. This research was also conducted to see whether learning by using comics does not make students feel difficult in learning Mathematics because the material will be changed in the form of conversation. The type of research used in this study is a quasi-experimental research. The treatment that will be given to the control class is in the form of comic media. While the experimental class does not use comics media, but the treatment for the experimental class is learning as usual in class. This research was conducted at SDN Teluk Santong. The number of subjects in this study were 39 students from class VI A and VI B SDN Teluk Santong. Based on the results of research, data analysis, and learning, it can be said that the learning outcomes achieved before the treatment was given to the two sample groups (Pre-Test) were lower than the treatment (Post-test) so that it could be said that there was an influence in the application of comic media. on the results of learning mathematics in the material of factors and multiples of class VI SDN Teluk Santong for the 2021/2022 academic year.